A novel DYRK1A (Dual specificity tyrosine phosphorylation‐regulated kinase 1A) inhibitor for the treatment of Alzheimer's disease: effect on Tau and amyloid pathologies in vitro. (26th January 2015) - Coutadeur, Séverine; Benyamine, Hélène; Delalonde, Laurence; de Oliveira, Catherine; Leblond, Bertrand; Foucourt, Alicia; Besson, Thierry; Casagrande, Anne‐Sophie; Taverne, Thierry; Girard, Angélique; Pando, Matthew P.; Désiré, Laurent
Abstract The dual‐specificity tyrosine phosphorylation‐regulated kinase 1A (DYRK1A) gene is located within the Down Syndrome (DS) critical region on chromosome 21 and is implicated in the generation of Tau and amyloid pathologies that are associated with the early onset Alzheimer's Disease (AD) observed in DS. DYRK1A is also found associated with neurofibrillary tangles in sporadic AD and phosphorylates key AD players (Tau, amyloid precursor, protein, etc). Thus, DYRK1A may be an important therapeutic target to modify the course of Tau and amyloid beta (Aβ) pathologies. Here, we describe EHT 5372 (methyl 9‐(2, 4‐dichlorophenylamino) thiazolo[5, 4‐f]quinazoline‐2‐carbimidate), a novel, highly potent (IC50 = 0.22 nM) DYRK1A inhibitor with a high degree of selectivity over 339 kinases. Models in which inhibition of DYRK1A by siRNA reduced and DYRK1A over‐expression induced Tau phosphorylation or Aβ production were used. EHT 5372 inhibits DYRK1A‐induced Tau phosphorylation at multiple AD‐relevant sites in biochemical and cellular assays. EHT 5372 also normalizes both Aβ‐induced Tau phosphorylation and DYRK1A‐stimulated Aβ production. DYRK1A is thus as a key element of Aβ‐mediated Tau hyperphosphorylation, which links Tau and amyloid pathologies. EHT 5372 and other compounds in its class warrant in vivo investigation as a novel, high‐potential therapy for AD and other Tau opathies. <boxed-text content-type="graphic" id="jnc13018-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Inhibition of the dual specificity tyrosine‐phosphorylation‐regulated kinase 1A (DYRK1A) is a new high‐potential therapeutic approach for Alzheimer disease. Here we describe EHT 5372, a novel potent and selective DYRK1A inhibitor. EHT 5372 inhibits DYRK1A‐induced Tau phosphorylation, Aβ production and Aβ effects on phospho‐Tau, including Tau aggregation.